แนวทางใหม่ในการพัฒนาครูโรงเรียนอัครสังฆมณฑลกรุงเทพฯ ตามอัตลักษณ์การศึกษาคาทอลิก - ดิษพล รุ่งโรจน์วรวัฒนา (จุฬาลงกรณ์มหาวิทยาลัย, 2020)
The purposes of this research were: 1) to study the current state of Catholic Education Identities of teachers in Bangkok Archdiocese 2) to study the current state, desirable state and needs assessment in teacher development of Bangkok Archdiocese Schools based on Catholic Education Identities and 3) to propose new approaches for teacher development of Bangkok Archdiocese Schools based on Catholic Education Identities. The research’s population is 37 catholic schools in Bangkok Archdiocese. Research Informants are 616 people, consisted of 37 administrators from each school, 37 directors of pastoral care from each school and 542 teachers from 37schools, which decresed from the first setting. The research instruments were 1) Questionnaire about the current state of Catholic education identities of teachers in the Bangkok Archdiocese and state and desirable state of teacher development of Bangkok Archdiocese based on Catholic Education Identities. And 2) The suitable and possibility assessment form for (draft of) new approach for teacher development of Bangkok Archdiocese based on Catholic Education Identities. The statistics used for data analysis consisted of frequency distribution, percentage, mean, standard deviation, PNI Modified analysis, mode and content analysis. The research findings showed that 1) in current state, most of Catholic Education Identities of teachers in Bangkok Archdiocese are in "high" complacent, but details are differed by each group of informants. 2) Studying the current state and desirable state of teacher development of Bangkok Archdiocese based on Catholic Education Identities showed Priority Need Index (PNI Modified) of each Identities. The highest PNI Modified of the first three identities were Identity no.7 "Growing mental life with each student directly and individually", which PNI Modified 0.300, Identity no.5 "Being an expert in teaching moral and religious teachings", which PNI Modified 0.275 and Identity no.3 "Joining every part of the community", which PNI Modified 0.272. And 3) the first three new approaches for teacher development of Bangkok Archdiocese based on Catholic Education Identities were to Workshop for developing "Growing mental life with each student directly and individually" Identity, to Workshop for developing "Being an expert in teaching moral and religious teachings" Identity and to create Professional Learning Community Workshop for developing "Joining every part of the community" Identity.